2016
DOI: 10.1007/s40565-016-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Business cases for energy storage with multiple service provision

Abstract: Energy storage (ES) has been considered as the key source of flexibility to support the integration of renewable energy. Previous studies have demonstrated the substantial system cost savings by the deployment of ES, including both investment and operation of generation, transmission and distribution infrastructure. However, this societal benefit may not be realized if industry actors do not have a viable business case to appropriately capture these multiple value streams. In this context, this paper investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…The continuous nature of steady-state reactive power provision means that the commitment of a BESS to this service would restrict its ability to provide other system services. In [11] the value of frequency response is shown to vary with time and it is suggested that the minimum value is at high demand. Conversely, reactive power services tend to have most value when demand is high as this is when voltage support related constraints are active.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous nature of steady-state reactive power provision means that the commitment of a BESS to this service would restrict its ability to provide other system services. In [11] the value of frequency response is shown to vary with time and it is suggested that the minimum value is at high demand. Conversely, reactive power services tend to have most value when demand is high as this is when voltage support related constraints are active.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of providing multiple simultaneous services with storage resources has generated active discussion throughout academia, industry, and government. The business case for multiple service provision in wholesale and retail markets is assessed by Teng and Strbac in [2]. Related economic analyses can be found in [3]- [5].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Related economic analyses can be found in [3]- [5]. In contrast to [2], which focuses on the aggregation of distributed storage systems, we concentrate on independently scheduled utility-scale systems.…”
Section: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [4] present a detailed review on the operation of hydro plants. The capability of energy storage to contribute simultaneously to energy and frequency service markets is analysed in [5,6]. In addition, energy storage systems are used to manage the variability of wind and PV generation in [7,8].…”
Section: Introductionmentioning
confidence: 99%